Budaya Kerja, Kepuasan Kerja Dan Kinerja Pegawai Pt. Trijaya Medika Farma: Motivasi Sebagai Moderator - Ardi Hidayat (Sains: Jurnal Manajemen dan Bisnis, 2017)
This study aims to obtain empirical evidence about the work culture, job satisfaction and performance of employees of PT. Trijaya Medika Farma and motivation as moderator. Where the employee is still not maximum performance especially discipline and high attendance levels so the impact on production targets were not achieved. The population in this study a total of 287 employees, and the sampling technique used purposive sampling with the formula slovin the study sample as many as 74 employees. This research is quantitative descriptive, namely research on the data collected and expressed in terms of numbers, though also in the form of qualitative data as supporters, such sentences are arranged in kuesioner. his research analysis tools using regression analysis statistical method. The result of the research shows that the work culture does not affect the employee's performance. Job satisfaction has a positive effect on the employee's performance, the motivation does not succeed moderate the work culture with the employee's performance, the motivation to moderate between job satisfaction and employee performance